Physics-based thermal management system components design for all-electric propulsion systems - Jafari, Soheil; Nikolaidis, Theoklis; Sureddi, Roopesh Chowdary (American Society of Mechanical Engineers (ASME), 2021)
Although electrification allows a significant reduction in fuel burn, noise, and emissions, one of the main challenges in this technology is to deal with the thermal loads generated by the electrified propulsion system components. This is to guarantee the safe and optimal operation of the propulsion system as well as the aircraft. This challenge needs to be addressed to enable this important technology to be adopted by aircraft manufacturers. This paper presents a methodological approach to calculate the heat load values generated by electric components in All-Electric Propulsion (AEP) architectures. Initially, the architecture of an AEP system will be presented and explained. Then, for each component, physics-based models based on associated heat loss mechanisms will be developed and presented. For this purpose, thermal models for battery packs, electric motors, inverters, and rectifiers are generated and a MATLAB/Simulink library is developed to calculate the thermal loads generated by each component at different working conditions. The developed models’ results are validated against publicly available data to confirm the effectiveness of the proposed approach. The simulation results confirm that the developed library is able to predict the thermal loads generated by lithium-ion battery packs, permanent magnet synchronous electric motors, multi-stage inverters, and rectifiers with less than 1%, 9.9%, 9.2%, and 0.5% errors respectively. Finally, an AEP architecture is simulated as the case study and the total heat loads generated by different components have been calculated at the design point to confirm the capability of the developed framework in system-level analyses.
Keywords: thermal management system; all electric propulsion; heat loss calculation; physics-based models; MATLAB toolbox